Discovery of a highly potent orally bioavailable imidazo-[1, 2-a]pyrazine Aurora inhibitor. Issue 8 (1st May 2018) - Yu, Tao; Zhang, Yonglian; Kerekes, Angela D.; Tagat, Jayaram R.; Doll, Ronald J.; Xiao, Yushi; Esposite, Sara; Hruza, Alan; Belanger, David B.; Voss, Matthew; Rainka, Matthew P.; Basso, Andrea; et al.
Graphical abstract: Abstract: Imidazo-[1, 2- a ]pyrazine1 is a potent inhibitor of Aurora A and B kinase in vitro and is effective in in vivo tumor models, but has poor oral bioavailbility and is unsuitable for oral dosing. We describe herein our effort to improve oral exposure in this class, resulting ultimately in the identification of a potent Aurora inhibitor16, which exhibited good drug exposure levels across species upon oral dosing, and showed excellent in vivo efficacy in a mouse xenograft tumor model when dosed orally.